2020
DOI: 10.1098/rspb.2020.0677
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of short- and long-term visual memories in an insect

Abstract: The formation of memories within the vertebrate brain is lateralized between hemispheres across multiple modalities. However, in invertebrates evidence for lateralization is restricted to olfactory memories, primarily from social bees. Here, we use a classical conditioning paradigm with a visual conditioned stimulus to show that visual memories are lateralized in the wood ant, Formica rufa . We show that a brief contact between a sugar reward and either the right or left antenna (reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
(115 reference statements)
1
8
0
Order By: Relevance
“…This emphasizes the importance of both MBs in memory view-based navigation in the CX. It also supports a unilateral influence of each MB on the CX control of the navigation behaviour, also supported by the evidence of lateralization in the insects' memory [66]. As such, there is an interesting correspondence to the model recently proposed by [44] in which the left and right MB are assumed to learn views oriented respectively to the left and right of the target direction.…”
Section: Discussionsupporting
confidence: 79%
“…This emphasizes the importance of both MBs in memory view-based navigation in the CX. It also supports a unilateral influence of each MB on the CX control of the navigation behaviour, also supported by the evidence of lateralization in the insects' memory [66]. As such, there is an interesting correspondence to the model recently proposed by [44] in which the left and right MB are assumed to learn views oriented respectively to the left and right of the target direction.…”
Section: Discussionsupporting
confidence: 79%
“…We have observed that ants with a unilateral lesion shift their walking direction towards the visual cue rather than to the location of the feeder 30° to its right, but this could potentially be due to some leftward bias in motor output, rather than specific disruption of navigational memory. Moreover, many behaviours are lateralised in insects, including aspects of learning and memory (reviewed in [14]), and wood ants are no exception showing lateralisation in behaviour [15] and memory formation [16].…”
Section: The Impaired Navigation From Unilateral Lesions Is Not a Motor Biasmentioning
confidence: 99%
“…This may be another line of evidence for lateralization in the insects' brain, which has received increasing attention in the last decade at both group/species ( Kells and Goulson, 2001 ) and individual levels ( Gaudry et al, 2013 ; Bell and Niven, 2014 ), particularly from an adaptive perspective ( Niven and Frasnelli, 2018 ; Frasnelli, 2013 ). In wood ants, it has been observed in behaviour such as trophillaxis ( Frasnelli et al, 2012 ) and memory encoding ( David Fernandes and Niven, 2020 ).…”
Section: Discussionmentioning
confidence: 99%